Australian administrative procedures (South Melbourne : Nelson, 1993)
This book is about: The office worker; Using the telephone; Processing the email; Producing documents and processing information; Filing and indexing; ...
Keywords: Office practice; Automation; Office practice -- Automation; Office management; Office practice; Office practice -- Problems, exercises, etc